Finding Appropriate Methods to Calculate Metal and Metal Hydride XPS Spectra - Jorstad, Jason (My University, 2012)
The goal of this study was to evaluate methods to calculate metal and metal hydride XPS (x-ray photoelectron spectra) from molecular structures.
Color poster with text, graphs, and tables.
Keywords: Metals--Analysis; Hydrides; Electron spectroscopy; Posters